1979
DOI: 10.1515/znc-1979-9-1029
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Analogues of Dibromothymoquinone and of Bromonitrothymol on Photosynthetic Electron Flow

Abstract: Alkyl substituted derivatives of halogenated p-benzoquinones, of halogenated /7-nitrophenols, and of 2,4-dinitrophenols were tested in the inhibition of photosynthetic electron flow in chloro plasts. The effect of the compounds on photoreductions by photosystem I or II, on a TMPD bypass in NADPH formation and the reversibility of the inhibition by dithiothreitol is used to distin guish between an inhibition site before or after plastoquinone function, i. e. between a DBMIB versus a DCMU inhibition pattern.It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…A chemically different group of inhibitors active at the Q B site was later developed-nitrophenols (like BNT = bromonitrothymol) by Trebst et al (1979) and Trebst and Draber (1986) and cyanophenols (like commercial ioxynil). There are differences in their inhibitory pattern as reviewed by Oettmeier (1999) and also below.…”
Section: Inhibition Of the Acceptor Side Of Photosystem IImentioning
confidence: 99%
“…A chemically different group of inhibitors active at the Q B site was later developed-nitrophenols (like BNT = bromonitrothymol) by Trebst et al (1979) and Trebst and Draber (1986) and cyanophenols (like commercial ioxynil). There are differences in their inhibitory pattern as reviewed by Oettmeier (1999) and also below.…”
Section: Inhibition Of the Acceptor Side Of Photosystem IImentioning
confidence: 99%
“…However, higher concentrations of DBMlB are able to block electron flow from Q to PQ [39. 60,187]. This was confirmed by Bowes and Crofts [20]: the Qoxidation decreased drastically in the presence of 2-20pM reduced DBMIB.…”
Section: Soriir Nriv Rlrcrron Rrunsporr Irihihirorsmentioning
confidence: 62%
“…When the water to MV assay was performed in the presence of ADP and Pi, rates of electron flow were about one-half the maximal uncoupled (+MA) rates. )2 evolution, and PSI C (12,22). However, we found poor rates of electron transport as a function of light when older tissue was used to isolate chloroplasts.…”
mentioning
confidence: 73%
“…2). Ascorbate DCBQ (Guikema, personal communications) but confirmation of nulation of oxidized this decline can be found in work presented by Trebst et al (22) icated with several where 100 lM DCBQ was found to inhibit NADP reduction as was less than 5%. well as O2 evolution.…”
mentioning
confidence: 82%